Analysing Tourism Expenses using Mathematical Modelling - ugli, Janzakov Bekzot Kulmamat; Beknazar, Sultonov; Islombek, Umirov; Aslbek, Utkirov; Madamin, Tursunboyev (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The article considers the ways a potential tourist would spend his/ her funds in three-day tour package in Samarkand city. For this purpose, a mathematical simulation model based on Monte Carlo method was used. As a result of the analysis, it was found that the total expenses of tourists were greatly influenced by the costs of transport and food.